1000 ideas by 100 architects - Costa Duran, Sergi; Eguaras, Mariana R. (Beverly, MA : Rockport, 2009)
Each architect brings something uniquely distinct to his or her work. Discovering what makes an architectural work or the body of an architect's work unique is difficult to deconstruct. 1000 Ideas by 100 Architects provides behind the scenes insight into the work of 100 top international designers through the deconstruction of 1000 architectural details and projects. --Publisher's description.
Keywords: Architects; Architecture, Modern -- 21st century